Application of the Pentahelix Model in the Preservation of Gibung Tradition to Increase the Attraction of Cultural Tourism in East Lombok - Mia Fidela; Ayuni Septiani Saputri; Tej Nafillah (Jurnal Indonesia Sosial Teknologi, 2025)
The Gibung tradition in Kelayu is a cultural heritage of religious and social significance as a tribute to TGH Umar, a great local scholar. In addition to commemorating the haul of TGH Umar, this tradition strengthens social relations and maintains the cultural identity of the community "Trio Kelayu Bersaudara." However, its sustainability faces challenges, mainly due to the declining participation of the younger generation and the influence of globalization. This study uses a qualitative method with a descriptive approach to explore the value and symbols in Gibung and identify the role of each pentahelix element (government, academics, business, society, and media) in its preservation. The results of the study show that pentahelix synergy is an effective strategy for maintaining the sustainability of Gibung amid modernization. The support of community participation plays an important role in ensuring that Gibung remains relevant for future generations and becomes a symbol of a rich cultural identity.